Prognostic and immune-related value of complement C1Q (C1QA, C1QB, and C1QC) in skin cutaneous melanoma - Yang, Huanglong; Che, Dehui; Gu, Yuxiang; Cao, Dongsheng (Frontiers in Genetics, 2022)
Background: Skin cutaneous melanoma (SKCM) is a common malignancy that is as-sociated with increased morbidity and mortality. Complement C1Q is composed of C1QA, C1QB, and C1QC, and is involved in the occurrence and development of many malignant tumours. However, the effect of C1QA, C1QB, and C1QC expression in tumour immunity and prognosis of cutaneous melanoma remains unclear. Methods: First, we analysed C1QA, C1QB, and C1QC expression and prognostic values using GEPIA and Tumour Immune Estimation Resource Analysis (TIMER) as well as further validation using RT-qPCR, the Human Protein Atlas, The Cancer Genome Atlas (TCGA) dataset, and Gene Expression Omnibus dataset. We then performed univariate/multivariate Cox pro-portional hazards model, clinicopathological correlation, and receiver operating characteristic curve analysis using the TCGA dataset and established a nomogram mod-el. Differentially expressed genes associated with C1QA, C1QB, and C1QC in SKCM were identified and analysed using LinkedOmics, TIMER, the Search Tool for the Re-trieval of Interacting Genes database, Metascape, and Cytoscape software. We used TIMER, GEPIA, and single-sample gene set enrichment analysis (ssGSEA) to analyse the relationship between the three genes and the level of immune cell infiltration, bi-omarkers, and checkpoint expression in SKCM. Finally, GSEA was utilized to study the functional pathways of C1QA, C1QB, and C1QC enrichment in SKCM. Results: Overexpression of C1QA, C1QB, and C1QC provided significant value in the diagnosis of SKCM and has been associated with better overall survival (OS). Mul-tivariate Cox regression analysis indicated that C1QA, C1QB, and C1QC were inde-pendent prognostic biomarkers for patients with SKCM. Immune cell infiltration, bi-omarkers, and checkpoints were positively correlated with the expression of C1QA, C1QB, and C1QC. Furthermore, the results of functional and pathway enrichment analysis showed that immune-related and apoptotic pathways were significantly en-riched in the high expression group of C1QA, C1QB, and C1QC. Conclusion: We found that C1QA, C1QB, and C1QC can be used as biomarkers for the diagnosis and prognosis of SKCM patients. The upregulated expression of these three complement components benefitted patients from OS and may increase the effect of immunotherapy. This result may be due to the dual effects of anti-tumour immunity and apoptosis.